2017
DOI: 10.5371/hp.2017.29.4.262
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Trochanteric Fragments in Cementless Bipolar Hemiarthroplasty of Unstable Intertrochanteric Fracture: Cerclage Wiring

Abstract: PurposeBipolar hemiarthroplasty (HA) is an option for the treatment of unstable intertrochanteric fracture in elderly patients. There is a raising concern regarding cable-grip related complications for the fixation of trochanteric fragments. Therefore, the aim of this study was to evaluate outcome of cementless HA with fixation for the trochanteric fragments using monofilament wires in unstable intertrochanteric fracture.Materials and MethodsWe reviewed 92 cementless bipolar HAs using a grit-blasted long stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Therefore, hemiarthroplasty is emerging as a viable alternative to internal fixation in recent decades. [1][2][3][4][5][6]8,[10][11][12] In this study, we retrospectively followed up 22 elderly patients of unstable intertrochanteric fractures treated by cemented bipolar hemiarthroplasty as the primary management plan. We observed that, hemiarthroplasty in the unstable fracture scenario is more challenging than the routine hemiarthroplasty surgeries for fractures of the neck of femur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, hemiarthroplasty is emerging as a viable alternative to internal fixation in recent decades. [1][2][3][4][5][6]8,[10][11][12] In this study, we retrospectively followed up 22 elderly patients of unstable intertrochanteric fractures treated by cemented bipolar hemiarthroplasty as the primary management plan. We observed that, hemiarthroplasty in the unstable fracture scenario is more challenging than the routine hemiarthroplasty surgeries for fractures of the neck of femur.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some researchers turn to cemented or uncemented hemiarthroplasty as an option to achieve a stable hip joint suitable for early weight-bearing rehabilitation. 3,5,[10][11][12] In the current study, we present our mid-term experience of managing the unstable intertrochanteric fractures in the elderly by cemented bipolar hemiarthroplasty and early rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the greater trochanteric and the medial fracture fragments were attached and fixed with two to three 16-gauge wires with the technique, which was described elsewhere. 16 Usually, the greater trochanter was fixed with one vertical wire, which was inserted through a hole drilled in the lateral femoral cortex below the abductor tubercle and a hole in the upper portion of the fractured greater trochanter. The medial fragment was fixed with one to two circumferential wires.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it was difficult to restore and adjust the leg length. To adjust the leg length, we used the method described by Lee et al 16 With the use of the trial components, the optimal stem size and head length were determined. If the size, stability, and leg length were satisfactory, the stem was inserted into the Journal of Orthopaedic Surgery 27 (2) femoral canal with a firm impaction from a gentle tapping to a press fit.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is not always possible for elderly patients with unstable fractures to have good outcomes after osteosynthesis (3,4). To address this problem, both improvement of surgical technique and advances in implant technology have been promoted (5)(6)(7)(8)(9). Therefore, intertrochanteric fractures need to be classified accurately to determine the most appropriate treatment method.…”
Section: Introductionmentioning
confidence: 99%